Ultra-high field neuroimaging in psychosis: A narrative review - Lavigne, Katie M.; Kanagasabai, Kesavi; Palaniyappan, Lena (Frontiers in Psychiatry, 2022)
Schizophrenia and related psychoses are complex neuropsychiatric diseases representing dysconnectivity across multiple scales, through the micro (cellular), meso (brain network), manifest (behavioral), and social (interpersonal) levels. In-vivo human neuroimaging, particularly at ultra-high field (UHF), offer unprecedented opportunity to examine multiscale dysconnectivity in psychosis. In this review, we provide an overview of the literature to date on UHF in psychosis, focusing on microscale findings from magnetic resonance spectroscopy, mesoscale studies on structural and functional magnetic resonance imaging, and multiscale studies assessing multiple neuroimaging modalities and relating UHF findings to behavior. We highlight key insights and considerations from multiscale and longitudinal studies and provide recommendations for future research on UHF neuroimaging in psychosis.